1996
DOI: 10.1063/1.471542
|View full text |Cite
|
Sign up to set email alerts
|

Auger decay of the dissociating core-excited states in the HCl and DCl molecules

Abstract: High-resolution Auger electron spectra from the decay of the Cl 2 p→* excitation in HCl and DCl have been measured. The spectra are analyzed, separating molecular and atomic features, which are assigned to transitions to the HCl ͑52͒ 4 * and Cl (3s3 p) 6 states, respectively. Auger line shapes, as affected by the molecular dissociation, are studied by comparing the experiment with the results of Monte-Carlo computer simulations based on a semiclassical model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 21 publications
3
29
1
Order By: Relevance
“…The kinetic energies of the resonant Auger electrons (for 1 S, 1 D and 3 P final states) were determined from the Cl + CIY from CH 3 Cl and were found to be approximately 177.3 eV, 179.3 eV and 180.7 eV, which are in good agreement with values reported earlier 8,48,49 .…”
Section: A1supporting
confidence: 79%
“…The kinetic energies of the resonant Auger electrons (for 1 S, 1 D and 3 P final states) were determined from the Cl + CIY from CH 3 Cl and were found to be approximately 177.3 eV, 179.3 eV and 180.7 eV, which are in good agreement with values reported earlier 8,48,49 .…”
Section: A1supporting
confidence: 79%
“…1 Following this work, ultrafast dissociation followed by Auger decay of atomic or molecular fragment has been observed for several molecules. [2][3][4][5][6][7][8][9][10][11] This body of work confirms that molecular Auger features coexist with fragment Auger lines, and therefore resonant Auger spectra provide a unique possibility to study the details of nuclear dynamics in core-excited molecular states. [12][13][14] Other interesting phenomena such as the Doppler effect in electron emission following ultrafast dissociation have also been observed in 4 is the relative intensity of below-threshold photoabsorption structures around the C 1s ionization threshold related to transitions to empty molecular orbitals versus Rydberg states: while the Rydberg series is dominant in methane, in tetrafluoromethane there are prominent broad structures at lower photon energy followed by a series of sharp peaks attributable to the Rydberg series.…”
Section: Introductionmentioning
confidence: 62%
“…[1][2][3] One of the most interesting phenomena involving molecular core-excitation has been the relation between core-excited dynamics and bond dissociation in the de-excitation process. Recent experimental investigation has shown that strong atomic displacement is induced in the coreexcited state, so that the molecular structure deformation in the core-excited state influences the following bond dissociation process.…”
Section: Introductionmentioning
confidence: 99%